PENGARUH RETURN ON ASSETS, RETURN ON EQUITY, INVESMENT OPPORTUNITY SET, TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MAKANAN DAN MINUMAN SUB SEKTOR BARANG KONSUMSI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Rifani Akbar Sulbahri; Nur Effen; Ari Martino (Universitas Tridinanti, 2022)
There is a phenomenon that shows that investors do not only see the company's ability to earn profits, but also the amount of use of debt by the company in carrying out its activities. Partial in food and beverage companies in the consumer goods sub-sector. The technique used in this research is the Qualitative Analysis method which analyzes data that is not in the form of numbers or figures in the form of explanations that cannot be expressed in numbers and the second method of Quantitative Analysis is a method that analysis is carried out on data in the form of numbers to apply an explanation of these figures. There are findings that the Company Value has a minimum value of 20.00, a maximum value of 973.00, an average value of 150.1944, and a standard value deviation of 221.29 887. The ROA variable has a minimum value of 3.00, a maximum value of 1778.00, an average value of 378.1389, and a standard deviation of 496.93346. The ROE variable has a minimum value of 8.00, a maximum value of 2791.00, an average value of 724.5000, and a standard deviation of 837.70136. The IOS variable has a minimum value of 2.00, a maximum value of 1409.00, an average value of 449.3889, and a standard deviation of 450.39667. F-test, shows that simultaneously the independent variables namely ROA, ROE, and IOS have no effect on the dependent variable, namely Firm Value, while Based on the results of the T test, this study shows that the results of testing the ROA variable have a significant effect on the firm value variable, ROE has no effect significant effect on the firm value variable, and IOS has a significant effect on the firm value variable.Keywords: return on assets, return on equity, investment opportunity set, and firm value